Frequency of Hypocalcemia among Patients with Moderate to Severe Chronic Plaque Psoriasis: Chronic Plaque Psoriasis - Ilyas, Saadia; Mukhtar, Rabia; Bashir, Bushra; Nusrat, Wajeeha; Ilyas, Tuyiba; Malik, Lamees Mahmood (Pakistan Journal of Health Sciences, 2023)
Psoriasis is a common skin problem. It is associated with many risk factors including hypocalcemia. It is important to determine serum calcium levels among psoriatic patients that may help in proper management. Objective: To determine frequency of hypocalcemia in patients of moderate to severe chronic plaque psoriasis. Methods: It was a cross-sectional study that had involved 90 patients of both genders aged between 22-70 years having chronic plaque psoriasis. The patients were evaluated for level of calcium in serum and hypocalcemia was labeled if albumin corrected serum calcium was <8.9 mg/dl. A prior written informed consent was taken from each patient. Results: The mean age of the patients was 40.7 ±1 3.9 years. There were 51 (56.7%) male and 39 (43.3%) female patients with a male to female ratio of 1.3:1. The mean duration of disease was 9.2 ± 4.4 years while the mean serum calcium was 8.89 ± 0.79 mg/dl. 59 (65.6%) patients had moderate while 31 (34.4%) patients had severe disease. Hypocalcemia was observed in 35 (38.9%) patients and it was significantly higher in patients with severe disease as compared to moderate disease (58.1% vs. 28.8%; p-value=0.007). Conclusions: In this study a substantial proportion of patients with chronic plaque psoriasis had hypocalcemia suggesting potential role of serum calcium in the pathogenesis of psoriasis. Hypocalcemia may also indicate severity of disease. This study advocates routine screening a correction of serum calcium levels among such patients as it leads to timely identification and appropriate management of the disease.